Optimalisasi Sistem Dan Desain CCTV Pada PT Jet Teknologi Express Berbasis Cloud - Handayani, Indri; Setiadi, Ade; Ridwan, Ade Muhamad (Technomedia Journal, 2019)
CCTV is a video camera device that serves to display and record an event at a time and place wherever the device is paired. CCTV stands for Closed Circuit Television. Cctv seing is used for the security system of a place whether it is office, shop, street or housing. This device becomes reliable when many cctv manufacturers are issuing the latest cctv output technology. Such as motion recording mode, auto line, alarm detector and many more. Therefore this device can be the most popular security tool nowadays. One company that uses cctv device as its security support is PT. Jet Technology Express. Almost all agents of PT. Jet Technology Express already installed cctv. Many benefits that can be obtained from the company with the cctv, among others, to monitor employee activities, monitoring the packet and its main function is to security agents spread across Indonesia. Keywords : CCTV, PT. Jet Teknologi Express, Secure